2015
DOI: 10.1016/j.physleta.2015.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Size and porosity effects on thermal conductivity of nanoporous material with an extension to nanoporous particles embedded in a host matrix

Abstract: Abstract.A formula for the effective thermal conductivity of nanoporous media is derived, following a thermodynamic approach. An extension to nanocomposites composed of a homogeneous matrix wherein porous nanoparticles are dispersed is proposed as well. The originality of the model is that it is based on extended irreversible thermodynamics, a theory specifically designed for sub-scaled systems. Two different situations are discussed, in the first one, nanoporous silicon with spherical porous inclusions of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…This is understandable since at larger pore sizes, the ballistic contribution becomes negligible with respect to the diffusive one ( ≪ 1) and Fourier's heat transfer is dominating. The effect of the porosity on the thermal conductivity is not to be investigated further, since it has been thoroughly studied in a previous work [22]. It is generally admitted that porosity reduces the thermal conductivity.…”
Section: Thermal Conductivity Of Bulk and Porous Siliconmentioning
confidence: 99%
See 2 more Smart Citations
“…This is understandable since at larger pore sizes, the ballistic contribution becomes negligible with respect to the diffusive one ( ≪ 1) and Fourier's heat transfer is dominating. The effect of the porosity on the thermal conductivity is not to be investigated further, since it has been thoroughly studied in a previous work [22]. It is generally admitted that porosity reduces the thermal conductivity.…”
Section: Thermal Conductivity Of Bulk and Porous Siliconmentioning
confidence: 99%
“…1. The corresponding values in the porous segment are obtained from the volumetric average of the silicon and air data [22]. Making use of these numerical values, it is found that the thermal boundary resistance coefficient and the Kapitza length are given by R=2.2*10 -9 m 2 K/W and ≈ 2 * 10 m. The latter result is significant as it justifies that the effect of interfacial thermal boundary resistance can be neglected for device lengths L longer than 2 µm, which represents a reasonable value within the context of the present work.…”
Section: Thermal Conductivity Of Bulk and Porous Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies (Jean et al, 2014), aMonte Carlo (MC) technique have been employed to extract geometry-determined for nanoporous bulk materials with selected periods and porosities. In other studies (Minnich and Chen, 2007;Machrafi and Lebon, 2015), simple expressions have been proposed to compute . However, some divergence can often be found between lattice thermal conductivities predicted by phonon MC simulations and by analytical models using .…”
mentioning
confidence: 99%
“…For larger nanoporous structures, phonon Monte Carlo (MC) simulations are employed, in which the exact structure geometry and frequency-dependent phonon mean free paths (MFPs) can both be incorporated [3,[27][28][29]. Other approaches include the discrete ordinate method [12,30,31], hybrid lattice dynamics-continuum mechanics technique [13,32], and various analytical models [13,24,[33][34][35][36].…”
mentioning
confidence: 99%